Rainfall Monitoring to Support Temporal and Spatial Information of Debris Flow Initiation in Merapi Volcano - Hairani, Ani; Rahardjo, Adam Pamudji; Legono, Djoko; Istiarto (International Journal of Integrated Engineering, 2021)
Debris flow frequently attacks rivers on slopes of Merapi Volcano and causes fatalities and damage of infrastructures. To reduce the risk of debris flow, a warning system has been developed by Sabo Office Center. Critical line and snake line graph are applied in Merapi Volcano to monitor characteristics of rainfall in the upland river basin. However, this warning system cannot predict the arrival time and location of the debris flow occurrence. Numerical simulation seems to be a good tool to improve its performance. This research proposed an idea to combine rainfall-based warning system with the numerical simulation model. This model used slope stability theory to identify debris flow initiation. Results of this research showed that fluctuation of rainfall intensity reflects changes of debris flow initiation area. The more severe rainfall intensity, the larger volume of surface flow, and thus the greater debris flow initiation takes place. When the rainfall monitoring is combined with the debris flow simulation results, there is a tendency of the enlargement of the debris flow area to follow the growth of the hourly rainfall.